Thermodynamic function of valineacid in n-n dimethyl formamide mixtures from conductance measurement (Baghdad Science Journal, 2013)
Some physical properties enthalpy (?H), entropy (?s), free energy (?G),capacities(?cp?) and Pka values) for valine in dimethyl foramideover the temperature range 293.15-318.15K, were determined by direct conductance measurements. The acid dissociation at six temperature was examined at solvent composition x2) involving 0.141 of dimethyl foramide . As results, calculated values have been used to determine the dissociation constant and the associated thermodynamic function for the valine in the solvent mixture over temperatures in the range 293.15-318.15 k. The Pka1, and Pka2 were increased with increasing temperature.